Troska o kulturę życia akademickiego jako realizacja funkcji wychowawczej uczelni - Kaczmarek, Żanetta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Academic culture, in the general sense of the term, which, in fact belongs to the larger area of social culture, constitute also a form of social culture, is the subject matter of the paper. Culture encompassing the whole of academic life, the multiplicity of forms, customs, language, tradition, ceremonial unites. Not only academic teacher together with a student create the culture, but culture creates them too. Academic culture consists of external aesthetics and also of the aesthetics of behaviour. Nowadays, the crisis in both can be seen. Students lack communicational skills, and their language is filled with vulgarism. Classes and lectures in social communication are conducted in many universities. It may contribute to facilitate the process of communication by making the utterances more understandable, meaningful and beautiful in terms of language. The postulated culture concerns also everyday language.
Keywords: ceremoniał; funkcje szkoły wyższej; kultura; programy kształcenia